ANALISIS SISTEM PENGENDALIAN INTERN TERHADAP PIUTANG PADA PT.DIVAINDO SENTRAL SARANA BANJARBARU - Maria Anastasia (Jurnal Ilmiah Ekonomi Bisnis, 2020)
ABSTRACT Ferry Setiawan, Department of Accounting Pancasetia College of Economics Banjarmasin, 2020, Analysis of Internal Control System of Accounts Receivable in PT.Divaindo Sentral Sarana Banjarbaru. Advisor 1 : Maria Anastasia, Advisor 2 : Pipit Angelia Widiarti. The objectives of this research are : 1) To analyze the internal control system of accounts receivable in PT.Divaindo Sentral Sarana. 2) To provide input on the internal control system of accounts receivable in PT.Divaindo Sentral Sarana that should be. This research is a qualitative research type. As for what is discussed in this study is an internal control system for accounts receivable and capability to minimize the value of uncollectible receivables from the PT.Divaindo Sentral Sarana. The results of this study indicate that the internal control system of accounts receivable in PT.Divaindo Sentral Sarana Banjarbaru is “Good Enough”, but it needs to be emphazised in the application of SOP and increased target from 93,5% to 98% so that can make a decrease in uncollectible accounts. Keyword : Internal Control System, Account Receivable